Weaving the Web. - Savage, Neil (Communications of the ACM, 2017)
The article discusses the development of the World Wide Web by inventor Tim Berners-Lee, noting his winning of the 2016 A.M. Turning Award. Topics include his work at the European Organization for Nuclear Research (CERN), his invention of Hypertext Transfer Protocol (HTTP) and Hypertext Markup Language (HTML), and his beliefs about Net neutrality and open access to Internet information.